Fazendo as palavras render: o inconsciente é infantil? (Revista de Estudos da Linguagem, 1993)
Morphologicaly-triggered humor is seen by somestudies as if itwas the result of free manipulations of certainlinguistic expressions.Hawever, it ispossible to show  that they  deal with a Iinguisticactivity governed by a very rigorousprincipIe, the equivalentof a morevulgar version of the Sassure'stheory of sign,the one that does not take into account his theory of value.Thepresent work analjyses a set of dataand seeks to demonstratethat this linguistic activity, which could "onIy be seenas ludic'reveals a particular way of functioningof language, based onapeculiar theory of literal meaning, inspite of contrary expectations.The central claim. is that, if this peculiar theoryof meamng isvalidfor every linguistic manifestation, language could notbe consideredstructure (this isa good anti-structuralist argument, by the way),but "nomenclatures", that is, lists of words.The result of thiswork adds to all  those which make up the assumption thatlanguagesarebetter analysed when viewed from various standpoints.